Find the general integral of
2x(y+z2)p+y(2y+z2)q=z2
"2x(y+z^2)p+y(2y+z^2)q=z^2\\\\\n2x(y+z^2)\\frac{\\partial z}{\\partial x}+y(2y+z^2)\\frac{\\partial z}{\\partial y}=z^2\\\\\n\\frac{dx}{2x(y+z^2)}=\\frac{dy}{y(2y+z^2)}=\\frac{dz}{z^2}\\\\\n\\text{Multiply through by } \\frac{xy}{xy}\\\\\ny\\frac{dx}{2xy^2+2xyz^2}=x\\frac{dy}{2xy^2+xyz^2}=xy\\frac{dz}{xyz^2}\\\\\n\\frac{ydx-xdy-xydz}{2xy^2+2xyz^2-2xy^2-xyz^2-xyz^2}=\\frac{ydx-xdy-xydz}{0}..........(1)\\\\\nydx-xdy-xydz=0\\\\\n\\text{Divide through by } xy\\\\\n\\frac{dx}{x}-\\frac{dy}{y}-dz=0\\\\\n\\text{Integrate through}\\\\\n\\ln x-\\ln y-z=a\\\\\n\\ln (\\frac{x}{y})-z=a"
Using "x, y, z" as multipliers. Each fraction if (1) will be
"\\frac{xydx-xydy-xyzdz}{2xy^2+2xyz^2-2xy^2-xyz^2-xyz^2}=\\frac{xydx-xydy-xyzdz}{0}\\\\\nxydx-xydy-xyzdz=0\\\\\n\\text{Divude through by } xy\\\\\ndx-dy-zdz=0\\\\\n\\text{Integrate}\\\\\nx-y-\\frac{z^2}{2}=b"
Therefore, the general solution is "f(\\ln (\\frac{x}{y})-z, x-y-\\frac{z^2}{2})=0"
Comments
Leave a comment